PERAN PENGELOLAAN LIMBAH DALAM MENINGKATKAN KEBERLANJUTAN UMKM BONIS COLLECTION DI DESA PELAMUNAN - Shafa Ula Khalisa; Riky Prawira; Rima Auliyanti; Melani Puspa Rangen; Lisda Simanjorang (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
This research aims to analyze the role of waste management in improving the sustainability of Bonis Collection bag craft UMKM in Pelamunan Village. Bonis Collection UMKM, which focus on producing bags from natural and recycled materials, face challenges in managing production waste so as not to damage the environment. This study uses a qualitative approach with a case study method, involving in-depth interviews with UMKM owners and workers, as well as direct observation at production sites. The research results show that implementing effective waste management strategies, such as recycling leftover materials and using environmentally friendly technology, can significantly increase the operational sustainability of UMKM. Apart from that, good waste management also has a positive impact on company image and customer satisfaction. The conclusions of this research emphasize the importance of waste management as an integral part of sustainable business practices for UMKM in the crafts sector.